Parenting intervention combined with acceptance and commitment therapy: A trial with families of children with cerebral palsy - Whittingham, K.; Sanders, M.; McKinlay, L.; Boyd, Roslyn (Oxford University Press, 2016)
Objective - to examine the effects of Stepping Stones Triple P (SSTP) and Acceptance and Commitment Therapy (ACT) on child functioning, quality of life, and parental adjustment. Method - 67 parents (97.0% mothers) of children (64.2% male; mean age 5.3 ± 3.0 years) with cerebral palsy participated in a randomized controlled trial with three groups: wait-list control, SSTP, and SSTP + ACT. This article details the secondary outcomes. Results - In comparison with wait-list, the SSTP + ACT group showed increased functional performance and quality of life as well as decreased parental psychological symptoms. No differences were found for parental confidence. No differences were found between SSTP and wait-list or between SSTP and SSTP + ACT. Conclusions - ACT-integrated parenting intervention may be an effective way to target child functioning, quality of life, and parental adjustment.